Comparative Analysis of the Health Level of Islamic Banks and Conventional Banks in Indonesia Before (2017-2019) and During Covid 19 (2020-2022) Using RGEC Method - Miptahudin, Iip; Nur Rizqi Rhommadhonni, Vania; Prabandari, Fitriana; Gemma Nurrahman, Ahmad (Journal of Economicate Studies, 2023)
This research aims to analyze the differences in the health of Sharia Banks and Conventional Banks in Indonesia before and during Covid-19. The research method used was quantitative descriptive using the RGEC method, data analysis using the Normality Test, and the Wilcoxon Signed Difference Test. The sampling technique used was a purposive sampling technique with the criteria of Islamic banks and conventional banks having core capital of less than 3 trillion. The samples obtained were 4 Sharia Commercial Banks and 7 Conventional Commercial Banks. The data comes from the bank's quarterly financial reports and GCG reports for the 2017-2019 (Before Covid-19) and 2020-2022 (During Covid-19) periods. The overall level of bank health using RGEC analysis shows that Sharia Commercial Banks are in a "Fairly Healthy" condition before and during the Covid-19 pandemic. Meanwhile, conventional commercial banks were in a "healthy" condition before and during the Covid-19 pandemic. The results of the Sign-Wilcoxon difference test show that comparing the health level of Islamic banks before and during the Covid-19 period, there is no difference in each ratio. Meanwhile, conventional banks have different ROA and ROE ratios, while there are no differences in the NPL, LDR, GCG, and CAR ratios.